Cysteamine protects gastric epithelial cell monolayers against drug induced damage: evidence for direct cellular protection by sulphydryl compounds. Issue 1 (January 1992) - Romano, M; Razandi, M; Raza, A; Szabo, S; Ivey, J
Abstract : The sulphydryl containing drug cysteamine protects gastric mucosa in vivo against acute injury. It is not known whether this protection includes a direct effect on gastric cells. Using gastric epithelial cell monolayers derived from a well differentiated human cell line, we evaluated whether cysteamine protects against taurocholate or indomethacin induced damage in conditions which completely exclude the influence of vascular, hormonal, and neural factors. The effect of cysteamine on prostaglandin production by monolayer cells in vitro was also assessed. Cysteamine decreased damage brought about by sodium taurocholate and indomethacin by 40% (p less than 0.01) and 50% (p less than 0.01) respectively. The sulphydryl blocker iodoacetamide prevented the protective effect of cysteamine. Pretreatment with indomethacin, which inhibited prostaglandin E2 output by 60%, did not prevent protection by cysteamine; incubation with cysteamine decreased prostaglandin E2 production by cultured cells. We conclude that (i) cysteamine directly protected gastric epithelial cells in vitro (ii) this protection occurred with indomethacin, which interferes with cellular metabolism of prostaglandins, and taurocholate, whose damaging action at neutral pH is unrelated to interference with prostanoid metabolism, (iii) cysteamine protection in vitro is unrelated to endogenous prostaglandins and is probably mediated by endogenous sulphydryl compounds.